Answer:
x = 3
y = -3
Step-by-step explanation:
We have two equations and are asked to solve for x and y.
y = -3x + 6
3y = -2x - 3
Substitute the y in the first equation in the second equation :
3(-3x + 6) = -2x - 3
Distribute :
-9x + 18 = -2x - 3
Solve for x by isolating it :
Subtract 18 from both sides :
-9x = -2x - 21
Add 2x to both sides :
-7x = -21
Divide -7 from both sides :
x = 3
Replace x in the first equation :
y = -3(3) + 6
y = -9 + 6
-9 + 6
y = -3
Step-by-step explanation:
m1.m2 = -1
18.m2 = -1
m2 = -1/18
formula = y - y1 = m2 ( x - x1)
y - (-5) = -1/18 ( x -1)
y + 5= -1x/18 +1/18
y = -1x/18 -89/18
Answer:
Scale using for plan ⇒ 1 m = 4 cm
Step-by-step explanation:
Hey, this is not a complete question, there is not visible graph. You may wanna retry to set up your question and make sure the graph is there
Answer:
3rd option
Step-by-step explanation: